Design and a Deep Customer Insight Approach to Innovation. Issue 2 (14th March 2016) - Price, Rebecca; Wrigley, Cara
ABSTRACT: This article proposes and explores the Deep Customer Insight Innovation Framework in order to develop an understanding as to how design can be integrated within existing innovation processes. The Deep Customer Insight Innovation Framework is generated from the results of a case study of Australian Airport Corporation seeking to drive airport innovations in operation and retail performance. The integration of a deep customer insight approach develops customer-centric and highly integrated solutions as a function of concentrated problem exploration and design-led idea generation. Businesses facing complex innovation challenges or seeking to make sense of future opportunities can integrate design into existing innovation processes, anchoring the new approach between existing market research and business development activities. This article contributes a framework and novel understanding as to how design methods are integrated into existing innovation processes for operationalization within industry.